2021
DOI: 10.3390/coatings11101267
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Application of Hexanal as a Surface Treatment Improved the Storage Life and Quality of Mango Fruits

Abstract: Mango is a highly preferred seasonal tropical fruit with a maximum shelf-life of five to seven days. Hexanal is a plant volatile compound assayed in green tissues and showing significance in enhancing storage life and fruit quality attributes by preserving membrane integrity. This experiment explored the effect of the pre-harvest application of an aqueous hexanal composition (active ingredient: 0.02% hexanal) in altering the post-harvest storage behavior of four mango cultivars. The pre-harvest application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…and reported that hexanal treatment reduced fruit browning and spoilage and extended the shelf life of various fruits during cold storage (Erika et al, 2020;Kaur et al, 2020). Hexanal treatment in mango fruits improved the shelf life and fruit quality, which would be sociated with improving cell membrane integrity (Preethi et al, 2021). Hexanal suppressed the activities of the cell wall-degrading enzymes, including PG, PME, and enzyme phospholipase-D, which is responsible for the deterioration of the fruits storage life (Kumar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…and reported that hexanal treatment reduced fruit browning and spoilage and extended the shelf life of various fruits during cold storage (Erika et al, 2020;Kaur et al, 2020). Hexanal treatment in mango fruits improved the shelf life and fruit quality, which would be sociated with improving cell membrane integrity (Preethi et al, 2021). Hexanal suppressed the activities of the cell wall-degrading enzymes, including PG, PME, and enzyme phospholipase-D, which is responsible for the deterioration of the fruits storage life (Kumar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the GRAS compound hexanal has been used effectively as a postharvest treatment for increasing shelf life, improving quality and reducing fruit loss of many climacteric and non‐climacteric horticultural products such as guava, 20 banana, 21 tomato, 22,23 capsicum, 24,25 mango, 26‐28 table grapes, 29 sweet cherry, 30 carnation 31 and rose 32 . Also, its excellent performance as a preharvest treatment has been reported in several fruit and vegetable species in terms of suppressing ripening and senescence as well as maintaining quality in guava, 33 mango, 34‐36 tomato, 37 nectarine 38 and apple 39 . The role of hexanal as an ethylene inhibitor for the downregulation of 1‐aminocyclopropane‐1‐carboxylic acid synthase was reported by Tiwari and Paliyath 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The sensor assessed the CO 2 and C 2 H 4 concentrations in the airtight container containing intact fruits of known quantity and weight. The CO 2 and ethylene results were expressed in mL of CO 2 /kg·h and μL of C 2 H 4 /kg·h, respectively. , …”
Section: Methodsmentioning
confidence: 99%
“…The CO 2 and ethylene results were expressed in mL of CO 2 /kg•h and μL of C 2 H 4 / kg•h, respectively. 6,25 Weight Loss. A digital balance (PS 3500/C/2, Radwag, EU) was used to determine the percent weight loss of guavas by weighing the identical fruit before and after storage.…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%